A Study on Stylistic Features and E-C Translation Skills of International Business Contract - Wu, chunrong (Advances in Social Sciences Research Journal, 2015)
Abstract:With China’s Reform and Opening-up Policy, especially her entrance into WTO, China’s international trades are mushrooming. As is known to all, most contracts of international trades are written in English which have intensely accurate vocabularies, well-structured organization and standardized forms. This paper analyzes international business contracts’ stylistic features such as lexical features, use of terminology, use of archaic words, juxtaposition of synonyms, frequent use of long sentences and passive tenses. Then the author tries to offer E-C translation skills correspondingly guided by Nida’s functional equivalence theory. It is believed that with a good understanding of the source text and command of both languages as well as related knowledge, E-C functional equivalence translation of IBC can be realized effectively.